Description of a new sandstone-dwelling species of genus Cnemaspis (Sauria: Gekkonidae) from Gunung Santubong National Park, southwestern Sarawak, Malaysia - Kurita, Takaki; Nishikawa, Kanto; Hossman, Mohamad Yazid; Mizuno, Takafumi; Sato, Hirotoshi; Gumal, Melvin (Zootaxa, 2024)
A newly discovered sandstone-dwelling species of the rock gecko, genus Cnemaspis, is described from Santubong National Park, 25 km north of Kuching, southwestern Sarawak, Malaysian Borneo. Molecular phylogenetic analysis confirmed that Cnemaspis puterisantubongae sp. nov. is closely related to other Cnemaspis species in southwestern Sarawak, except for C. kendallii, although these relationships remain unclear. The new species differs from closely related species in having a moderate snout–vent length of up to 66.7 mm; 10–14 precloacal pores in males; 9–14 obviously-convex precloacal pore-bearing scales in females; enlarged, smooth, flat median subcaudal scales; sharp-edged, broad black markings on the trunk dorsum; and a black–gray banding pattern on the posterior part of the original tail, with white median subcaudal scales in males. This discovery of this new species from Santubong National Park, which is highly accessible due to its proximity to Kuching, highlights the need for extensive inventory surveys throughout the national parks of Sarawak.